Characterisation of flavour profile of beef jerky inoculated with different autochthonous lactic acid bacteria using electronic nose and gas chromatography–ion mobility spectrometry. (January 2022) - Wen, Rongxin; Kong, Baohua; Yin, Xiaoyu; Zhang, Huan; Chen, Qian
Abstract: The flavour profiles of beef jerky separately inoculated with different autochthonous lactic acid bacteria (LAB) strains ( Lactobacillus sakei BL6, Pediococcus acidilactici BP2, and Lactobacillus fermentum BL11) and a non-inoculated control were analysed using electronic nose (E-nose) and gas chromatography–ion mobility spectrometry (GC–IMS). GC–IMS results revealed a total of 42 volatile compounds in beef jerky. Inoculation of the three LAB strains decreased the levels of lipid autoxidation-derived aldehydes (e.g., hexanal, heptanal, octanal, and nonanal). In addition, inoculation of P. acidilactici BP2 increased the levels of esters. Principal component analysis of the E-nose and GC–IMS results could effectively differentiate non-inoculated beef jerky and beef jerky separately inoculated with different LAB strains. Furthermore, there was a high correlation between the E-nose and GC–IMS results, providing a theoretical basis for the identification of different beef jerky formulations and selection of autochthonous starter cultures for beef jerky fermentation. Highlights: The application of E-nose and GC–IMS could effectively differentiate beef jerky. W1W, W1S, W5S, W2W, and W2S sensors were sensitive to beef jerky flavours. Three lactic acid bacteria strains decreased the levels of aldehydes. Inoculation of Pediococcus acidilactici BP2 increased the levels of esters.